POLA PEMANFAATAN GUA-GUA HUNIAN PRASEJARAH DI KALIMANTAN SELATAN DAN TIMUR - Sugiyanto, Bambang (Naditira Widya, 2009)
The physiography of Kalimantan comprise a vast range of karst potential for prospective scientific research and development, particularly, archaaeological and cultural studies; karst offers an invaluable data in regard to human benefiting from ones enviroment including setting up a dwelling place in a cave or rockshelter thousands of years ago. Evidences of cave dwellers have been found in the southeastern and eastern part of Kalimantan. This article discusses patterns employed by human in choosing and benefiting from caves as either temporary or permanent dwelling place in the past.